2021
DOI: 10.1021/acssuschemeng.1c02542
|View full text |Cite
|
Sign up to set email alerts
|

Wear Mechanism Analysis of a New Rotary Shear Biomass Comminution System

Abstract: A new biomass comminution system, Crumbler rotary shear, was developed to process fuel-grade biomass. The rotary shear is more efficient than the traditional hammer mill in comminuting high-moisture biomass and producing more uniform particles with minimal fines. However, the milling unit experiences significant wear in processing dirty woodchips. This study investigated the wear mechanisms of the rotary shear system based on analysis of the minerals carried by woodchips and characterization of actual worn com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Its application to biomass encounters well-known difficulty of pulverization. 14) A most reasonable way to solve this problem is heat treatment that allows mild pyrolysis, i.e., torrefaction. Yu et al 15) and Wang et al 16) showed great improvement in pulverizability of biomass in terms of time or energy consumption by torrefaction at temperatures of 220-325°C.…”
Section: Introductionmentioning
confidence: 99%
“…Its application to biomass encounters well-known difficulty of pulverization. 14) A most reasonable way to solve this problem is heat treatment that allows mild pyrolysis, i.e., torrefaction. Yu et al 15) and Wang et al 16) showed great improvement in pulverizability of biomass in terms of time or energy consumption by torrefaction at temperatures of 220-325°C.…”
Section: Introductionmentioning
confidence: 99%
“…Still, this finite element analysis made it possible to compare the contact pressures for different wood species and/or woodchip shapes, thereafter to provide useful information for the cutter blade design. For example, such an analysis suggested that the current square cutter tooth (DZ design) can break woodchips more efficiently than the previous sharp curvy tooth design in our earlier report (Lee et al, 2021). The improved performance of the DZ design has been validated on actual rotary shear systems at Utilizing this finite element simulation method, initial effort has been carried out for optimizing the DZ tooth design.…”
Section: Discussionmentioning
confidence: 95%
“…High contact pressure at these contact locations brings up continuum damage to the cutters and gradually downgrades their functionality. The wear mechanisms could include several types, such as abrasive wear, surface fatigue, erosive wear, and corrosion wear, as detailed in Lee et al, (2021). However, a high contact pressure on the cutter surface is expected to result in high tangential friction on the cutter surface and accumulate more heat under continuous working conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wibawa et al applied the above-mentioned sequence to coke production from softwood alone while inserting torrefaction before pulverization in consideration of the effectiveness of fine pulverization for increasing the coke strength, difficulty of pulverization of biomass, and improvement of pulverizability of biomass by torrefaction. , Then, Wibawa et al prepared cokes with tensile strengths of 10–32 MPa without any additives. The strength of coke from pulverized softwood (<100 μm) with hot briquetting but without torrefaction was smaller than 5 MPa.…”
Section: Introductionmentioning
confidence: 99%